Boecio y la división de las ciencias especulativas en el De Trinitate - Pascual, L.C., Rafael (Alpha Omega, 2018)
Summary: Boethius can be considered the ideal middleman between the Greek-Roman classical world and the medieval one. His influence in western thought is difficult to gauge. In the article we point out the continuity of thought between Aristotle, Boethius, and successively Thomas Aquinas, in a very important epistemological question: the division of the speculative sciences. Boethius addresses the topic on two occasions: in the first commentary to Porphyry's Isagoge, and in the brief treatise De Trinitate. After presenting both texts, and verifying the different philosophical contexts in which they are, we tackle the disputatio that arose aver the illegitimate interpretation of some authors of the text of De Trinitate, based on the doctrine of the degrees of abstraction.